PENGUKURAN KINERJA PRODUKSI FURNITURE FLOORING BERBASIS METODE SUPPLY CHAIN OPERATION REFERENCE PADA UD. AZB - Agachi, Muhammad Rigam; Mahbubah, Nina Aini (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
This research aims to measure the supply chain performance of a furniture company located in Gresik Regency, namely UD. AZB. In its production process, not only growth occurs but the company also faces problems, including a lack of product marketing strategies and miscommunication between the owner and suppliers, the owner and workers, and the owner and customers. Supply Chain Operation References (SCOR) is the methodological approach used in this research. In addition, weighting was also applied to each core process, attribute, and Key Performance Indicators. Meanwhile, snorm de bour normalization was used to standardize the values of the Key Performance Indicators. The results of the production performance measurement of flooring furniture at UD. AZB obtained 14 KPIs. The production performance value is 84.58 good indicators. This research is expected to help improve the performance of UD. AZB by conducting evaluations and enhancements in areas that are still lacking in order to increase customer satisfaction.